Thermal Performance of Novel Eco-Friendly Prefabricated Walls for Thermal Comfort in Temperate Climates - Alavez-Ramirez, Rafael; Chiñas-Castillo, Fernando; Martínez-Reyes, Jacobo; Caballero-Montes, José Luis; Caballero-Caballero, Magdaleno; Morales-Dominguez, Valentin Juventino; Ortiz-Guzmán, Margarito; Robledo-Taboada, Luis Humberto; Juárez Arellano, Erick Adrián; Serrano-De la Rosa, Laura Elvira (Sustainability, 2024)
The global threat of climate change has become increasingly severe, with the efficiency of buildings and the environment being significantly impacted. It is necessary to develop bioclimatic architectural systems that can effectively reduce energy consumption while bringing thermal comfort, reducing the impact of external temperatures. This study presents the results of a real-scale experimental house prototype, MHTITCA, using a unique design composed of novel eco-friendly prefabricated channel walls filled with a blend of soil, sawdust, and cement for walls and roofs. The experimental analysis performed in this study was based on dynamic climatology. A solar orientation chart of the place was constructed to identify the solar radiation intensity acting on the house. Measurements of roof surface temperatures were conducted to determine temperature damping and temperature wave lag. Monthly average temperature and direct solar radiation data of the site were considered. Compared to other alternative house prototypes, the system maximizes thermal comfort in high-oscillation temperate climates. Temperature measurements were taken inside and outside to evaluate the thermal performance. A thermal insulating layer was added outside the wall and the envelope to improve the prototype’s thermal comfort and reduce the decrement factor even more. This MHTITCA house prototype had 85% thermal comfort, 0% overheating, and 15% low heating. This eco-friendly prototype design had the best thermal performance, achieving a thermal lag of twelve hours, a reduced decrement factor of 0.109, and preventing overheating in areas with high thermal fluctuations. Comparatively, the other prototypes examined provided inferior thermal comfort. The suggested MHTITCA system can be an energy-saving and passive cooling option for thermal comfort in low-cost houses in temperate climates with high thermal oscillations in urban or rural settings.
Keywords: Inercia térmica; Refrigeración pasiva; Sostenibilidad